2017
DOI: 10.1007/s00421-017-3757-z
|View full text |Cite
|
Sign up to set email alerts
|

Recovery following a marathon: a comparison of cold water immersion, whole body cryotherapy and a placebo control

Abstract: The findings show WBC has a negative impact on muscle function, perceptions of soreness and a number of blood parameters compared to CWI, contradicting the suggestion that WBC may be a superior recovery strategy. Further, cryotherapy is no more effective than a placebo intervention at improving functional recovery or perceptions of training stress following a marathon. These findings lend further evidence to suggest that treatment belief and the placebo effect may be largely responsible for the beneficial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 50 publications
6
75
3
3
Order By: Relevance
“…Although participants in the present study were not informed of the study hypothesis and a control intervention was used for comparison, we did not examine the potential influence of the placebo effect on the observed responses. Accumulating evidence indicates that therapeutic effects of popular recovery modalities, such as cryotherapy, stem at least partially from a placebo effect (53,54). These important observations emphasize the need for future studies on the effects of HT to implement an effective placebo-controlled design.…”
Section: Discussionmentioning
confidence: 99%
“…Although participants in the present study were not informed of the study hypothesis and a control intervention was used for comparison, we did not examine the potential influence of the placebo effect on the observed responses. Accumulating evidence indicates that therapeutic effects of popular recovery modalities, such as cryotherapy, stem at least partially from a placebo effect (53,54). These important observations emphasize the need for future studies on the effects of HT to implement an effective placebo-controlled design.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by Mawhinney et al, (2017) who demonstrated that limb blood flow is reduced to a greater extent following CWI than WBC. Further, research from our group has evaluated the efficacy of CWI and WBC on performance following a trail marathon and found that WBC negatively impacted the recovery of muscle function compared to CWI, and that neither intervention was more effective than a placebo (Wilson et al, 2018). Presently, there do not appear to be any other studies directly comparing the effectiveness of the two different cryotherapy modalities on functional recovery after resistance exercise.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, there appears to be increasing evidence that many of the therapeutic effects attributed to cryotherapy treatment may be due to a placebo effect (Broatch, Petersen, & Bishop, 2014;Wilson et al, 2018). Currently, the vast majority of cryotherapy studies have been conducted using a control group, and have not taken expectance effect or treatment belief into account when reporting study outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Wilson et al (2017) compared the effects between WBC (3 minutes at −85°C, followed by a 15‐minute resting period under ambient environmental conditions, followed by 4 minutes at −85°C) and CWI (10 minutes at 8°C) following a marathon in healthy males. These authors only observed a trivial effect in MVIC recovery between 24 and 48 hours after the CWI treatment, and WBC was reported to have a negative effect on MVIC at 48‐hour post‐exercise . In a follow‐up study, Wilson et al (2018) observed that WBC, using a similar cooling protocol, was more effective compared with CWI (10 minutes at 10°C) to attenuate perceptual and functional recovery following resistance training in males .…”
Section: Introductionmentioning
confidence: 99%
“…These authors only observed a trivial effect in MVIC recovery between 24 and 48 hours after the CWI treatment, and WBC was reported to have a negative effect on MVIC at 48-hour post-exercise. 12 In a follow-up study, observed that WBC, using a similar cooling protocol, was more effective compared with CWI (10 minutes at 10°C) to attenuate perceptual and functional recovery following resistance training in males. 13 However, the mechanism of muscle damage between the aforementioned studies all varied, with two studies employing primarily mechanical damage (Abaidia et al 2016; while the other study consisted of primarily metabolic damage (Wilson et al 2017).…”
mentioning
confidence: 99%